Bound in the Bond of Life : Pittsburgh Writers Reflect on the Tree of Life Tragedy - Lidji, Eric; Kissileff, Beth (Book collections on Project MUSE., 2020)
On October 27, 2018, three congregations were holding their morning Shabbat services at the Tree of Life Synagogue in Pittsburgh's Squirrel Hill neighborhood when a lone gunman entered the building and opened fire. He killed eleven people and injured six more in the deadliest anti-Semitic attack in American history. The story made national headlines for weeks following the shooting, but Pittsburgh and the local Jewish community could not simply move on when the news cycle did. The essays in this anthology, written by local journalists, academics, rabbis, and other community members, reveal a city's attempts to cope, make sense of, and come to terms with an unfathomable horror. Here, members from the three impacted congregations are able to reflect on their experiences in a raw, profound way. Local reporters who wrote about the event professionally contribute stories that they were unable to articulate until now. Activists consider their work at a calm distance from the chaotic intensity of their daily efforts. Academics mesh their professional expertise with their personal experiences of this shattering event in their hometown. Rabbis share their process of crafting comforting messages for their constituents when they themselves felt hopeless. By bringing local voices together into a chorus, they are raised over the din of national and international chroniclers who offer important contributions but do not and cannot feel the intensity of this tragedy in the same way as locals. The essays in this anthology tell a collective story of city shaken to its very core, but determined that love will ultimately win.